Culinary MSMEs with Halal Certification: Resilience Factors During the Covid-19 Pandemic - Andika, Sultan (Jeksyah: Islamic Economics Journal, 2023)
The presence of COVID-19 has implications on the global economy, including Indonesia. Economic downturns are not only experienced by large multinational and national companies but also impact micro, small, and medium enterprises (UMKM). This study aims to investigate the resilience factors of UMKM during the COVID-19 pandemic, with the intention of deriving survival strategies specifically tailored to UMKM in this challenging period. Research data was gathered through interviews with 100 UMKM owners in the food and beverage sector, comprising both those with halal certification and those without in Palu City. Subsequently, the UMKM were categorized into resilient and non-resilient groups for further analysis. The research methodology applied for this study involved descriptive analysis and logistic regression analysis. Based on the research findings, the factors that positively and significantly influence UMKM resilience during the COVID-19 pandemic are entrepreneurial characteristics and government support.